175k views
1 vote
Simplify: 5(x+6)−(5−x)−6x

1 Answer

3 votes

Answer:

25

Explanation:

5(x+6)−(5−x)−6x

Remember PEMDAS

P – Parentheses

E – Exponents

M – Multiplication

/D – Division (whichever comes first from left to right)

A – Addition

/S – Subtraction (whichever comes first from left to right)

First, let's distribute the left side:

5 * x = 5x

5 * 6 = 30

5x + 30

Now, lets distribute the right side

-(5 - x) = -1(5 - x)

-1 * 5 = -5

-1 * -x = x ( - * - = +)

x - 5

Now we have:

5x + 30 + x - 5 - 6x

Let's combine like terms.

5x, -6x, and x are like terms. 5x + x = 6x - 6x = 0

30 and -5 are like terms. 30 - 5 = 25

25

Since we can't simplify this any further, that is our answer.

~
InLoveWithPugs

Moderator

Math Enthusiast

User Jaeho
by
6.0k points